(untitled) (Journal of Informatics Education and Research, 2024)
The biotechnology sector is characterized by rapid technological advancements, intense competition, and dynamic market conditions. For start-ups operating in this space, the ability to capture and leverage competitive intelligence (CI) is crucial for gaining a strategic edge. This research paper explores the role of competitive intelligence in enhancing the competitiveness and sustainability of biotech start-ups. It delves into strategies for collecting, analyzing, and applying market insights to inform decision-making, optimize resource allocation, and drive innovation. The paper highlights best practices in CI, common challenges faced by biotech start-ups, and solutions to overcome these barriers. Through an in-depth examination of CI frameworks and real-world case studies, the research underscores how well-executed competitive intelligence can position biotech start-ups for long-term success. The findings contribute to a clearer understanding of how start-ups can build robust CI processes and use them to adapt to market changes, identify growth opportunities, and mitigate risks.